THE GRADUATE CURRICULUM IN ACCOUNTING. - Vincent, Vern H. (The Accounting Review, 1954)
Abstract It is difficult to consider the graduate curriculum entirely apart from the undergraduate curriculum. The graduate curriculum must allow considerable adjustment to the needs of individual students. This is even more true of graduate students than of the undergraduates in view of their greater diversity of background. Applicants to the graduate school will range all the way from the man who was an accounting major as an undergraduate, to the liberal arts graduate who majored in mathematics or English or to the law school product of twenty years ago. Some hopeful graduate students, therefore, may need to concentrate on "broadening" their training. Others who have had their share of this diversification will desire and will need to devote most of their time to accounting. Of one thing one can be reasonably certain about the graduate students: few, indeed, will have moved very far in their undergraduate days toward developing their capacity in communication and in independent, critical thought. In these modern times it seems students just cannot get time for those fundamentals in the first sixteen years of training in school.